Smart Antennas and Electromagnetic Signal Processing for Advanced Wireless Technology : With Artificial Intelligence Applications and Coding - Hoole, Paul R. P. (River Publishers, 2020)
The book addresses the current demand for a scientific approach to advanced wireless technology and its future developments. It gives a clear presentation of both antennas and adaptive signal processing which is what makes antennas powerful, maneuverable and necessary for advanced wireless technology. The book presents electromagnetic signal processing techniques that both control the antenna beam and track the moving station, which is required for effective, fast, dynamic beamforming. The first part of the book presents a comprehensive description and analysis of basic antenna theory, starting from short dipole antennas to array antennas. This section also includes important concepts related to antenna parameters, electromagnetic wave propagation, the Friis equation, the radar equation and wave reflection and transmission through media. The second part of the book focuses on smart antennas, commencing from a look at the traditional approach to beamforming before getting into the details of smart antennas. Complete derivation and description of the techniques for electromagnetic field signal processing techniques for adaptive beamforming are also presented. Artificial Intelligence (AI) driven beamforming is presented using computationally fast and low-memory demanding technique for AI beamforming is presented with the different excitation functions available. A novel method for fast, low memory and accurate, maneuverable single beam generation is presented, as well as other methods for beamforming with fewer elements along with a simple method for tracking the mobile antenna and station. In this section, for completeness, the use of antenna signal processing for synthetic aperture techniques for imaging is also presented, specifically the Inverse Synthetic Aperture Imaging technique. The third part of the book presents technological aspects of advanced wireless technology, including the 5G wireless system and the various devices needed to construct it. While the books' main emphasis is theoretical understanding and design, it includes applications, and legal matters are also presented.
Keywords: Wireless communication systems.; Adaptive antennas.; Antennas (Electronics) -- Design and construction.; Signal processing -- Digital techniques.; Adaptive signal processing.; elektronické knihy; electronic books